A computational investigation on the total cavopulmonary connection circulation assisted by an axial flow pump - Jin, Can; Liu, Xudong; Wu, Yong; Wang, Shengzhang; Zhu, Junming (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveFontan surgery constructs Total Cavo-Pulmonary Connection Circulation (TCPC), but lacks power. Cavopulmonary circulation assist devices (CPAD) has been proposed to support the Fontan circulation. The virtual implantation of blood pumps into the real TCPC structure to analyze the output characteristics of blood pump and flow pattern can better guide design of the pump and the formulation of powered Fontan surgical protocols.MethodWe used computational fluid dynamics (CFD) to explore the power assistance effect of an axial flow blood pump when it was virtually implanted in the real TCPC structures of patients with Fontan circulation and analyzed the differences between constant-speed pumps and variable-speed pumps.ResultsNumerical simulation results showed that the implantation of the blood pump increases pulmonary circulation blood flow by 32.6%, significantly improving the uneven distribution of flow in the left and right pulmonary arteries (the left/right pulmonary artery flow ratio improved from 1:1.8 to 1:1.2). The constant-speed pump mode increased hepatic venous return flow by 19.4% compared to baseline conditions, whereas the variable-speed pump improved it only by 12.7%. The constant-speed pump generated more stable spiral flow patterns in the TCPC structure, reducing energy loss by 21.3% compared to the variable-speed pump, and the wall shear stress distribution in the inferior vena cava (IVC) region was found to be closer to physiological conditions.ConclusionsAccording to the results, we confirm that the constant speed mode in powered Fontan circulation has significant advantages in maintaining blood flow stability, optimizing energy efficiency, and promoting organ-specific venous return.